Diversity of biocontrol agents, isolated from several sources, inhibitory to several fungal plant pathogens - Yan Ramona; IDA BAGUS GEDE DARMAYASA; ANAK AGUNG NGURAH NARA KUSUMA; Martin Line (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ramona Y, Darmayasa IBG, Kusuma AANN, Line MA. 2021. Diversity of biocontrol agents, isolated from several sources, inhibitory to several fungal plant pathogens. Biodiversitas 22: 298-303. This study investigated the inhibitory potential of diversity of antagonist bacteria residing in the rhizosphere zone and mature compost to counter fungal plant pathogens. Soils collected from rhizosphere of lettuce farms in Bali-Indonesia and Tasmania-Australia, mature compost, commercial biocontrol (Dipel®), and laboratory contaminants with significant inhibition against tested fungal pathogens were used as sources of antagonist bacteria. These antagonists were isolated by applying dilution and spread method on trypticase soya agar (TSA) or potato dextrose agar (PDA), and their ability to inhibit Sclerotinia minor, Sclerotinia sclerotiorum, Fusarium spp., and Rhizoctonia solani was assessed in dual culture assays. The results showed that 67 out of more than 100 isolates had antagonistic activity in vitro against at least one of tested fungal pathogens. In the preliminary identification, Bacillus spp. or Pseudomonas spp. were found to be pre-dominant isolates. Following screening studies in a non-replicated glasshouse experiment against S. minor and S. sclerotiorum, 8 of the most promising isolates were further identified using molecular methods based on their 16s rDNA sequences aligned with those deposited at the GeneBank. These 8 isolates were identified as Pseudomonas corrugata, Bacillus megaterium, Bacillus polymyxa, Bacillus mojavensis, Bacillus pumilus, Bacillus thuringiensis, Exiguobacterium acetylicum, and Chryseobacterium indologenes.